Professional identity and gender socialization: a study from school textbooks in democratic Spain - Guichot Reina, Virginia; De la Torre Sierra, Ana María (Historia y Memoria de la Educación, 2020)
The construction of professional identity is a concept that holds interest for a variety of disciplines such as Anthropology, Psychology or Pedagogy. From the perspective of social constructivism, it has a narrative, dynamic character and is shaped by the interaction of the subject with current socio-historical discourses and their interiorization. During the decade of the nineteen seventies, the labor market in Spain experienced a massive incorporation of women, brought about by social and legislative advances in education and employment. The years of Spanish democracy are essential in the configuration and renewal of female identity in the economic field. This article focuses on the influence of the school textbook - the main didactic resource used in formal education - in this configuration. It presents models and stereotypes linked to gender, with a potential influence on the transmission and configuration of a biased socio-labor culture. In order to study this influence, our research examines a total of 20 elementary education textbooks in the areas of Language and Social Sciences in two periods of democratic Spain —the so-called Transition period and the current moment—, to explore the professional identity of women linked to the economic socialization as this is conveyed through this educational tool. Our results reveal a minimal inclusion of women as economic subjects in the textbooks; the underrepresentation of females performing paid activities, as well the lack of professional diversity serve to highlight a substantial inequality in the socialization processes between men and women, contrary to the goals of coeducational teaching values.